Functional analysis of novel A20 variants in patients with atypical inflammatory diseases - Saori Kadowaki; Kunio Hashimoto; Toyoki Nishimura; Kenichi Kashimada; Tomonori Kadowaki; Norio Kawamoto; Kohsuke Imai; Satoshi Okada; Hirokazu Kanegane; Hidenori Ohnishi (Arthritis Research & Therapy, 2021)
Abstract Background A20 haploinsufficiency (HA20) is an early-onset autoinflammatory disease caused by mutations in the TNFAIP3 gene, which encodes the protein A20. Numerous truncating mutations in the TNFAIP3 gene have been reported in HA20 patients, whereas fewer missense variants have had their pathogenicity confirmed. Here, we evaluated the pathogenic significance of three previously unreported missense variants of the TNFAIP3 gene in suspected cases of HA20. Methods We obtained the clinical features and immunological data of three patients with missense variants (Glu192Lys, Ile310Thr, and Gln709Arg) of unknown significance of TNFAIP3. We then performed in vitro functional assays including analysis of nuclear factor (NF)-κB reporter gene activity, detection of A20 expression and phosphorylation of A20 by IκB kinase β (IKKβ), and K63-deubiquitination assay using TNFAIP3-deficient HEK293 cells. Three known pathogenic missense mutations reported previously were also investigated. Results The inhibitory effect on NF-κB reporter gene activity was significantly disrupted by A20 Glu192Lys and the three known mutations. The variants Ile310Thr and Gln709Arg did not show a difference from the wild type in any of the assays performed in this study. Conclusions Among the three variants in the TNFAIP3 gene, Glu192Lys was interpreted as being likely pathogenic, but Ile310Thr and Gln709Arg as being not pathogenic (uncertain significance and likely benign, respectively), based on the American College of Medical Genetics and Genomics standards and guidelines. Our study highlights the necessity of performing in vitro functional assays, notably, NF-κB reporter gene assay, to evaluate the pathogenicity of TNFAIP3 missense variants for the accurate diagnosis of HA20.